JAKARTA ISLAMIC INDEX: COVID-19 PANDEMIC AND POTENTIAL FINANCIAL DISTRESS - Nugroho, Avianto; Wasiaturrahma, Wasiaturrahma; Anggia, Putri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
This research aims to analyze the potential for financial distress of Islamic companies that are included in the Jakarta Islamic Index during pandemic of COVID-19, which is using profitability ratios, liability ratios, and liquidity ratios (Zwesky's Model). The sample is quarterly (2019 to 2020) and it is using the Generalized Method of Moments (GMM) panel data model approach that was developed by Arellano and Bond (1991). The results of this study indicate that the profitability ratio has the most influence on corporate financial distress and from the overall this research occurs in the process of decreasing company financial performance during pandemic of COVID-19. Moreover, there is one company that indicates financial distressed, there are twenty-two companies that experienced a decline in financial performance, but there are 7 companies that experiences better financial performance when the COVID-19 pandemic occurred. In one hand, this shows that COVID-19 has a broad effect on the decline in the financial performance of sharia companies. On the other hand, it has a positive impact on certain companies that works specifically in sectors which is related to information technology.